Primary splenic abscess in an adult female patient: a case report - Burce Isik; Matthew G. Davey; Sarah Gaffney; Patrick J. Stapleton; Javier Mohigefer; Efthymios Koutroumanos (Surgical Case Reports)
Abstract Background Primary splenic abscess is rare and typically presents in patients who are immunocompromised. We present a case of a 47-year-old apparently immunocompetent female patient who was diagnosed with primary splenic abscess from a Salmonella Typhimurium infection following emergency laparotomy. Case presentation A 47-year-old female patient presented with subjective fever and severe epigastric and left flank pain. She was treated empirically with intravenous piperacillin/tazobactam and gentamicin and was resuscitated with intravenous crystalloid infusion. A radiological diagnosis of splenic infarct secondary to splenic artery aneurysm superimposed with splenic abscess was presumed, however at emergency laparotomy, primary splenic abscess was identified. This abscess had eroded the left hemidiaphragm and had ruptured the splenic capsule leading to intra-abdominal pus in the pelvis which on culture grew Salmonella Typhimurium. A splenectomy and primary repair of the left hemidiaphragm were performed, with postoperative pancreatitis diagnosed following the procedure. After intensive care treatment, this patient made a full recovery. Conclusion This case of primary splenic abscess was treated successfully with a combination of surgery (i.e.: splenectomy and surgical drainage), prolonged antimicrobial therapy, and intensive care in the perioperative period.